Karakterisasi Morfologi Bunga dan Buah Abnormal Kelapa Sawit (Elaeis guineensis Jacq) Hasil Kultur Jaringan - Helen Hetharie; Gustav A. Wattimena; Maggy Thenawidjaya S.; Hajrial Aswidinnoor; Nurita Toruan-Mathius; Gale Ginting (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2007)
Tissue culture-derived plants of oil palm (Elaeis guineensis Jacq) can produce abnormal female dan male flowers, especially female, which develop into mantled fruit. This abnormality have caused yield lost up to 40%. The objectives of this research were to study the stages of flower development in which the abnormality started to appear, to characterize the morphology of the abnormal flower and fruit, and to determine the degree of abnormality. Plant materials used in this research were MK152, MK 176, MK 203, MK163, MK104, MK 212 and MK 209 clones obtained from the collection of